Supercapacitor based on Multi-walled Carbon Nanotubes/Carbon Black Composites-coated Wooden Sheet - Paweena Dulyaseree; Wirat Jarernboon; Winadda Wongwiriyapan (My University, 2014)
Supercapacitor consists of two carbon electrodes and wooden sheet as a separator. Three types of carbon electrodes were prepared; carbon black (CB), multi-walled carbon nanotubes (MWNTs) and composites of MWNTs and CB (MWNTs-CB). Electrode pastes were coated on both sides of wooden sheet. The thickness of wooden sheet was varies from 1 mm to 5 mm. The morphology of CB, MWNTs and MWNTs-CB were characterized by scanning electron microscopy (SEM). The supercapacitor performance was characterized by cyclic voltammetry and galvanostatic charge/discharge techniques. Among carbon electrode materials, MWNTs-CB shows the highest specific capacitance. The high specific capacitance of MWNTs-CB may be due to the high surface area of MWNTs incorporated with CB acting as spacer for MWNTs agglomeration protection and electrolyte- electrode accessibility improvement. Moreover, wooden sheet with a thickness of 2 mm shows the highest specific capacitance.
Keywords: Carbon fibers; Separator (oil production); Supercapacitor Materials and Fabrication